Analisis Pengaruh Kinerja Keuangan Perusahaan terhadap Financial Distress pada Industri Material Bangunan yang Terdaftar di BEI - Wilasittha, Acynthia Ayu; Sadzili, Rohan As (Jurnal Akuntansi AKUNESA, 2024)
Companies that continue to experience a decline in performance are feared to face financial difficulties. After understanding this problem, companies are expected to improve their financial performance. Financial ratio analysis is targeted at making companies and investors aware of the financial performance in the building materials industry. The method used in this research is quantitative method. The data source in this study was obtained from the individual financial statements of each building material industry listed on the BEI. This study uses the Mann Whitney Difference Test to test the difference between Altman Z-Score and Springate. In this study, it is known that the Altman Z-Score and Springate methods have significant differences. The financial performance results using Altman Z-Score are lower than Springate. During the pandemic, the B-121 sector industry experienced financial difficulties because its revenue decreased while its operating costs remained. From this research, it is hoped that investors can carefully choose the method and place of investment.